Evidence-Based Analysis of Social Impact Bonds for Homelessness: A Scoping Review - Wang, Huan; Xu, Xiaoguang (Frontiers in Psychology, 2022)
Social impact bonds (SIBs) have emerged as an innovative financial instrument designed to support the social service sector in delivering innovative social programs. In particular, SIBs can be used to finance prevention of homelessness among those regarded as vulnerable. There is little evidence that outcomes from SIB-funded programs are significantly different compared to more traditional programs. This is the first scoping review of academic and grey literature that explores main features and outcomes from all SIBs for homelessness based on evidence, addressing an important gap in the literature. The scoping review provided a transparent and comprehensive approach for mapping areas of this research. A total of 73 studies and articles were found eligible for inclusion; these concerned 32 SIBs for homelessness implemented in the United Kingdom, the United States, Australia, and Belgium. The review found that academic papers on SIBs for homelessness lack evidence-based analysis, while grey literature lacks transparency, especially in evaluation method and outcome. We found that fourteen projects met their target outcomes; the common features of these SIBs were a navigator intervention model, effective partnership working, and use of Special Purpose Vehicles. Our findings show that it is necessary for the managers of SIBs to improve outcome metrics and evaluation methods, support target groups fairly, and attract more private investors to finance SIBs for better addressing homelessness.